“Evaluating Cervical Cancer Screening Uptake And Awareness Among Women In Bhopal, Madhya Pradesh: A Community-Based Cross-Sectional Study” - Vishwakarma, Pinki; Rachna, Rachna; Agraha, Trashi Singh; Dubey, Akansha (Journal of Neonatal Surgery, 2025)
N